2017
DOI: 10.1186/s12888-016-1165-2
|View full text |Cite
|
Sign up to set email alerts
|

Did you get any help? A post-hoc secondary analysis of a randomized controlled trial of psychoeducation for patients with antisocial personality disorder in outpatient substance abuse treatment programs

Abstract: BackgroundPeople in treatment for substance use disorder commonly have comorbid personality disorders, including antisocial personality disorder. Little is known about treatments that specifically address comorbid antisocial personality disorder.MethodsSelf-rated help received for antisocial personality disorder was assessed during follow-ups at 3, 9 and 15 months post-randomization of a randomized trial of psychoeducation for people with comorbid substance use and antisocial personality disorder (n = 175).Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…The role of psychoeducation has been studied in patients with ASPD comorbid with substance use in at least one RCT. [ 83 84 85 ] In this, a total of 176 patients were randomized into two groups: treatment as usual ( n = 80) or treatment as usual plus a psychoeducation program (i.e., impulsive lifestyle counseling) ( n = 96). The diagnosis of ASPD was made using the Mini International Neuropsychiatric Interview [MINI] ASPD module while addiction severity index was used for assessing the severity of substance dependence.…”
Section: Management Aspects Of Comorbid Pd and Sudsmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of psychoeducation has been studied in patients with ASPD comorbid with substance use in at least one RCT. [ 83 84 85 ] In this, a total of 176 patients were randomized into two groups: treatment as usual ( n = 80) or treatment as usual plus a psychoeducation program (i.e., impulsive lifestyle counseling) ( n = 96). The diagnosis of ASPD was made using the Mini International Neuropsychiatric Interview [MINI] ASPD module while addiction severity index was used for assessing the severity of substance dependence.…”
Section: Management Aspects Of Comorbid Pd and Sudsmentioning
confidence: 99%
“…[ 83 ] A post hoc analysis of the data also reported increased perceived help for anti-social PD among participants. [ 85 ] At the 3-month follow-up, the perceived help was associated with more abstinent days, higher treatment satisfaction rates, and reduced rate of dropping out of treatment. Overall, from this study, it may be concluded that psychoeducation may add beneficially to the treatment compliance and retention in patients with ASPD and substance use.…”
Section: Management Aspects Of Comorbid Pd and Sudsmentioning
confidence: 99%
“…Bernstein et al, 2012;D.P. Bernstein et al, 2021;Doyle et al, 2016) and CBT (Crawford et al, 2009;B. Thylstrup et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…These medicines are useful if there is anxiety or depression, or if the person uses the substance to treat themselves for anxiety or low mood. [19][20][21]…”
Section: Discussionmentioning
confidence: 99%